Heart rate variability threshold and blood lactate response during constant load exercises - Zanatta, Carolina; Matsushigue, Karin Ayumi; Nakamura, Fábio Yuzo; De-Oliveira, Fernando Roberto (Journal of Physical Education (Maringá), 2008)
The aim of this study was to determine the blood lactate response and Heart Rate Variability response (VFC) during exercises with constant loads below, above and at the load of heart rate variability threshold (LVFC). Fifteen subjects performed a progressive exercise for LVFC determination and three constant load exercises (CC) in the following loads: 0.5 kp above (Ac-LVFC), 0.5 kp below (Ab-LVFC) and in the LVFC. LVFC was accepted as the first work load associated with VFC lower than 3 ms. Blood lactate values at 15th min in the Ac-LVFC, LVFC and Ab-LVFC loads were, 7.5 (±3.5), 4.4 (±2.3) and 2.4 (±1.0) mmol.l-1, respectively. Twenty five percent of the subjects showed a blood lactate steady-state in Ac-LVFC, 64% at LVFC and 93% in Ab-LVFC. The results showed that the LVFC may be above the first lactate threshold.